No spamming please guys
Attachments:
![](https://hi-static.z-dn.net/files/dde/8a2d495201cb9e3fca04203acf729457.jpg)
Answers
Answered by
7
EXPLANATION.
(a + b), b, (a - b) are in continuous proportion.
As we know that,
For continuous proportion.
⇒ b² = ac.
⇒ b² = (a + b)(a - b).
As we know that,
Formula of :
⇒ (x² - y²) = (x - y)(x + y).
Using this formula in the equation, we get.
⇒ b² = a² - b².
We can write equation as,
⇒ b² + b² = a².
⇒ 2b² = a².
To show :
⇒ a²/b² = 2.
Put the value of a² = 2b² in the equation, we get.
⇒ 2b²/b² = 2.
Hence proved.
Similar questions
CBSE BOARD X,
1 month ago
Economy,
3 months ago
Math,
3 months ago
English,
11 months ago
Hindi,
11 months ago